Effects of Lignophenols on Mechanical Performance of Biocomposites Based on Polyhydroxybutyrate (PHB) and Polypropylene (PP) Reinforced with Pulp Fibers - Hao Ren; Zhulan Liu; Huamin Zhai; Yunfeng Cao; Shigetoshi Omori (BioResources, 2014)
The effects of lignophenols and pulp fibers as reinforcing elements in biocomposites were studied with poly-(3-hydroxybutyrate) (PHB) biopolymers and polystyrene (PS) matrix materials. Lignophenols and (NH2(CH2)3Si(OC2H5)3) were compared as plasticizing or compatibilizing additives in tests of composite properties. PHB and PP were blended with pulp fiber cellulose and lignophenol by torque rheometer, and the test specimens were processed via injection moulding. Various testing methods, including tensile and impact tests, SEM, XRD, TGA, and ART-FTIR were used to investigate the properties of the composites. PHB and PP-cellulose fiber composites with strong mechanical properties could be created by using a torque rheometer as a mixer at 190 ºC with very short mixing times. The (NH2(CH2)3Si(OC2H5)3) was found to improve the mechanical features of the PP, but not very obviously for both tensile and impact strengths of PHB. However, the lignophenols positively affected the PHB-pulp fiber composites. In summary, a novel method has been demonstrated for creating biodegradable composites with pulp fibers in the absence of a coupling agent, and lignophenols may be applicable as an additive in the cases described in this study.